“It should be much faster fashion”— textile industry stakeholders’ perceptions of a just circular transition in Tamil Nadu, India - Anna Härri; Jarkko Levänen (Discover Sustainability, 2024)
Abstract There is a need for a paradigm shift to circular, sustainable textile systems. The transition will have impacts on people and businesses around the world, yet research on the circular economy has been overly focused on the economic and environmental dimension, lacking in the social dimension. Without design for comprehensive justness, the transition can reproduce or lead to novel injustices. We use distributive, procedural, and recognitive justice dimensions to analyze and uncover justness aspects related to the circular transition in the textile industry in Tamil Nadu, India. Our qualitative analysis is based on interviews with stakeholders of the industry. We uncover several justness tensions related to economic, social, power, value, epistemic, and governance issues. For the just circular transition to succeed, the tensions should at the very least be acknowledged, and ameliorated or dealt with when possible. The building blocks for this process are, for example, codesign of private governance systems, sharing the costs of the transition more equally and inclusion of various voices in knowledge production. As a step forward from the current situation in which a circularity focused approach and a justness focused approach emphasize different aspects, we present a new framework for designing just circular transitions, one that bring these important perspectives together.